Nations Within a State and the Emerging Hydrocarbons Industry in Uganda - Taodzera, Shingirai (Université d'Ottawa / University of Ottawa, 2020)
This research investigates the shifting political settlements between the Ugandan state and the Bunyoro and Buganda kingdoms after the discovery of oil between 2007 and 2018. It seeks to answer the following questions using a historically, theoretically, and empirically grounded investigation: What accounts for the Bunyoro kingdom’s failure to benefit substantially from the discovery of oil on its territory? What lessons can be learnt from the Buganda kingdom’s relative success in negotiating with the central government and developing its own political and economic capacity independently of the state? The Bunyoro kingdom, located in the oil-rich Albertine Graben region of western Uganda, has failed to access significant economic benefits from the country’s emerging oil sector despite its historical ownership of the land on which the resource is found. This dissertation combines political settlements theory and the concept of extraversion to explain this empirical puzzle. It finds that the ruling National Resistance Movement (NRM)’s imposition of an exclusive political settlement in Uganda, coupled with the Bunyoro kingdom’s limited holding power, accounts for the kingdom’s failure to derive financial benefits from the oil sector. The relative marginalisation of the Bunyoro from Uganda’s oil sector results from the NRM’s historical strategy of limiting the power of sub-state groups who are subsequently excluded from the governing coalition. The main beneficiaries of the oil industry in Uganda are political elites within the ruling NRM coalition and their close associates. The Buganda kingdom serves as a control case study and reveals the potential strategies and structural changes the Bunyoro kingdom could pursue to potentially bypass Uganda’s exclusive settlement and therefore benefit from the country’s nascent oil sector. This dissertation also engages with broader debates on the struggles between the state and traditional kingdoms since independence in sub-Saharan Africa and how this intersects with the politics of natural resource governance. Since the inception of the modern state in the colonial era, kingdoms have engaged in a complex and dialogic relationship of indifference, cooperation, and contention with successive governing regimes. Some of the kingdoms challenged and resisted, albeit unsuccessfully the colonial imposition of a central state primarily because it led to their loss of political and economic power. Ultimately, the state and the kingdoms represent dual forms of nationality forced to co-exist in the post-colonial era, and this produces a complex mix of cooperation, contestation and strategic coexistence. The management and exploitation of natural resources, including oil, is embedded in this political context, and is often associated with adverse outcomes, such as rent-seeking, authoritarian governance, and sectarian violence. Some of these dynamics have accompanied the emergence of Uganda’s new oil industry, with political contestation occurring between the state and the Bunyoro kingdom which has unsuccessfully attempted to capture a share of oil revenue.
Keywords: Natural resource governance; Traditional authorities; Political settlements; Strategic coexistence; Oil industry; State formation